A novel method for designing thermo-active retaining walls using two-dimensional analyses. Issue 3 (16th June 2022) - Sailer, Eleonora; Taborda, David M.G.; Zdravković, Lidija; Potts, David M.
Abstract : Thermo-active retaining walls are geotechnical structures employed as heat exchangers to provide low carbon dioxide heating and cooling to buildings. To assess the thermo-mechanical response of such structures, finite-element (FE) analyses are typically carried out. Due to the presence of heat exchanger pipes, the temperature distribution along the width of the wall is not uniform, implying that these problems are three-dimensional (3D) in nature. However, performing 3D FE analyses including elements to model the heat exchanger pipes to simulate the advective conductive heat transfer as well as thermo-hydro-mechanical coupling to reproduce the non-isothermal soil response accurately requires considerable computational effort. In this work, a novel approach to simulate thermo-active walls in 2D analyses was developed, which requires the sole use of thermal boundary conditions. This approach was found to reproduce average wall behaviour computed in 3D to a high degree of accuracy for numerous wall geometries, a wide range of thermal properties of soil and concrete, and different thermal boundary conditions along the exposed face of the wall. In addition, out-of-plane effects recorded in 3D analyses were assessed and an accurate simplified procedure to account for these when performing 2D analyses was developed.